Itraconazole solid dispersion prepared by a supercritical fluid technique: preparation, in vitro characterization, and bioavailability in beagle dogs [Corrigendum] - Yin X; Daintree LS; Ding S; Ledger DM; Wang B; Zhao W; Qi J; Wu W; Han J (Dove Medical Press, 2015)
Yin X, Daintree LS, Ding S, et al. Drug Des Devel Ther. 2015;9:2801–2810.On page 2801, please note the additional author.Xuezhi Yin1,3Linda Sharon Daintree2Sheng Ding3Daniel Mark Ledger2 Bing Wang3Wenwen Zhao2Jianping Qi1 Wei Wu1Jiansheng Han31Department of Pharmaceutics, School of Pharmacy, Fudan University, Key Laboratory of Smart Drug Delivery of Ministry of Education, Shanghai, 2Crystec Pharma Tianjin Research Centre, Tianjin, 3Changzhou Pharmaceutical Factory, Changzhou, People’s Republic of ChinaRead the original article